miRNA–protein–metabolite interaction network reveals the regulatory network and players of pregnancy regulation in dairy cows - Chatterjee, Bhaswati; Thakur, Suman S. (Frontiers in Cell and Developmental Biology, 2024)
Pregnancy is a complex process involving complex molecular interaction networks such as between miRNA-protein, protein-protein, metabolite-metabolite and protein-metabolite interactions. Advances in technology have led to the identification of many pregnancy associated microRNAs (miRNAs), proteins and metabolites fingerprints in dairy cows. An array of miRNAs, proteins and metabolites fingerprints produced during the early pregnancy of dairy cows were described. We have found the in silico interaction networks between miRNA-protein, protein-protein, metabolite-metabolite and protein-metabolite. We have manually constructed miRNA - protein – metabolite interaction networks such as bta-miR-423-3p - IGFBP2 - PGF2α interactomes. This interactome is obtained by manually combining the interaction network formed between bta-miR-423-3p - IGFBP2 and the interaction network between IGFBP2 - PGF2α with IGFBP2 as a common interactor with bta-miR-423-3p and PGF2α with provided evidences. The interaction between bta-miR-423-3p and IGFBP2 has many evidences including a high miRanda score of 169, minimum free energy (MFE) score of -25.14, binding probability (p) of 1, energy of -25.5. The interaction between IGFBP2 and PGF2α occurs at high confidence scores (≥ 70). Interestingly, PGF2α is also found to interact with different metabolites such as PGF2α - PGD2, PGF2α - thromboxane B2, PGF2α - PGE2, PGF2α - 6-keto-PGF1α at high confidence scores (≥ 70). Further, the interactions between C3 - PGE2, C3- PGD2, PGE2 - PGD2, PGD2 -thromboxane B2, PGE2 - thromboxane B2, 6-keto-PGF1α - thromboxane B2, PGE2 - 6-keto-PGF1α were also obtained at high confidence scores (≥ 70). Therefore, we propose that miRNA-proteins-metabolites interactomes involving miRNA, proteins and metabolites fingerprints of early pregnancy of dairy cows such as bta-miR-423-3p, IGFBP2, PGF2α, PGD2, C3, PGE2, 6-keto-PGF1 alpha, and thromboxane B2 may form the key regulatory networks and players of pregnancy regulation in dairy cows. This is the first study, involving miRNA-proteins-metabolites interactomes obtained in the early pregnancy stage of dairy cows.